2015
DOI: 10.1590/1809-4430-eng.agric.v35n2p322-330/2015
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de Mentha aquatica cultivada em sistemas alagados construídos sob diferentes taxas de aplicação orgânica

Abstract: RESUMO:Em vista da escassez de informações sobre o comportamento da espécie Mentha aquatica quando cultivada sob condições de alagamento e altas concentrações orgânicas, objetivou--se avaliar o efeito de diferentes taxas de carregamento orgânico (TCOs) sobre a produtividade e o estado nutricional da espécie cultivada em sistemas alagados construídos (SACs) de escoamento horizontal subsuperficial no tratamento de efluente primário de esgoto sanitário. Dois SACs de 24,0 m x 1,0 m x 0,35 m, preenchidos com brita … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…According to Table 5, it is observed that as the amount of chemical fertilizer decreases, the concentration of nutrients in the tissues decreases. Work carried out by Avelar et al (2015) in the Mentha aquatica variety, found this same situation when organic fertilizer increased. The element that presented the highest concentration in the leaves and stems was nitrogen.…”
Section: Resultsmentioning
confidence: 64%
“…According to Table 5, it is observed that as the amount of chemical fertilizer decreases, the concentration of nutrients in the tissues decreases. Work carried out by Avelar et al (2015) in the Mentha aquatica variety, found this same situation when organic fertilizer increased. The element that presented the highest concentration in the leaves and stems was nitrogen.…”
Section: Resultsmentioning
confidence: 64%
“…In recent decades, there has been a growing interest in constructed wetlands (CWs) systems, as they are simple, low cost, and easy to operate and maintain for treating a wide range of wastewater, such as domestic (Avelar et al, 2015), dairy products (Matos et al, 2012;Mendonça et al, 2015), pig farming (Fia et al, 2015), textile industry (Saeed & Sun, 2013), and compounds from pharmaceutical industries (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Constructed Wetlands Systems (CWS) can be a promising technical alternative, since it is a simple, low cost and easy operation and maintenance technology for the treatment of a wide variety of wastewater, such as domestic (Avelar et al, 2015), of dairy products Mendonça et al, 2015), of swine farming (Sarmento et al, 2012;Fia et al, 2015), of textile industry (Saeed & Sun, 2013) and drugs industry (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%